Assessment of Drinking Water Quality Status and its Impact on Health in Tandojam City - Arslan Mumtaz; Muhammad Saffar Mirjat; Hafeez ur Rehman Mangio; Aashifa Soomro (Journal of Basic & Applied Sciences, 2017)
Unsafe drinking water is one of the major concerns in developing countries. The southern Sindh is province of Pakistan that adjoins the Arabian Sea coast where the drinking water quality is deteriorating due to unrefined urban waste and excessive use of agro-chemicals. Present study aimed to assess the quality of ground water source and to compare it with WHO standards. Water borne diseases associated with drinking it in the vicinity Tandojam city were identified. Water from ground water source was sampled at selected locations in the study area. The samples were collected mostly from pumped waters. The samples were analyzed for physico-chemical properties in order to identify the quality problems and suggest safe source for drinking purpose. Findings revealed that the ground water quality in Muzaffrabad colony is deteriorating. The situation was much worse in Muzaffrabad colony, Jam Ghar and Mir colony with high TDS and salty taste, respectively at few sampling locations. In addition, laboratory analysis of the water quality parameters revealed the detail of variation in the groundwater. TDS, hardness, sodium (Na), chloride (Cl) and magnesium (Mg) etc. were considerably beyond the WHO permissible limits. The poor quality of the water has created different waterborne diseases like cholera, diarrhea etc. Moreover, the samples of SAU Colony and Amar Town showed that the water quality of these areas was within acceptable limits according to WHO standards and was suitable for the purpose of drinking.